Mycobacterium szulgai Pulmonary Infection in an Immunocompromised Patient - Neves, Sara (2023)
Mycobacterium szulgai is a slow-growing nontuberculous mycobacterium (NTM). It was first described in 1972 and is responsible for less than 0.2% of all NTM infections. The most common presentation resembles pulmonary tuberculosis, but it may also present as an extrapulmonary disease. It primarily affects individuals with underlying lung disease or immunocompromising conditions. The increasing use of tumor necrosis factor-alpha inhibitors, such as adalimumab, is associated with an increased risk of serious infections. We report a case of Mycobacterium szulgai infection in a 23-year-old woman with a history of childhood pneumonia and Crohn's disease on adalimumab.